Prevalence of reproductive conditions in canines - JOSEPH, CECILIA; KULASEKAR, K; ARAVIND, AMRITHA; THILAGAR, S (The Indian Journal of Animal Reproduction, 2005)
The prevalence of reproductive conditions in canines were analysed from 2498 clinical cases presented to the Small Animal Gynaecology and Obstetrics Unit of Madras Veterinary College hospital during the year 1999 to 2001. The incidence of physiological conditions (61.9%) like breeding advice and pregnancy diagnosis were higher than the pathological disorders (38.1%) like pseudopregnancy, anestrum, medical termination of pregnancy, pyometra, dystokias, postpartum conditions and venereal tumors. Higher incidences of reproductive conditions were recorded during South West Monsoon (27.94%). Majority of the reproductive problems occurred in bitches aged 1 to 2 years (42.31 %) and in the Spitz breed (38.71 %).